KEPENTINGAN KOREA SELATAN MENJALIN KERJASAMA DENGAN VIETNAM MELALUI KOREA ODA (OFFICIAL DEVELOPMENT ASSISTANCE) - Larasati "; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
South Korea has become a major partner of Foreign Development Assistance to Vietnam after the restoration of Strategic Cooperation between the two countries. Korea in particular gave Vietnam the largest part of ODA in the form of loans and grants. This research was prepared using the prespective of Liberalism, the theory of Foreign Aid and the concept of National of Interest. This Research used descriptive qualitative research methods which is the research data was obtained through literature review and library research. This study aims to determine Korea interests behind the large and consistent contribution of ODA to Vietnam. As for the feedback Vietnam provides a favorable business climate for Korea with several conditions namely first, through LOI and LOE regulations governing companies and investments in VietnamThis study indicate that Vietnam has made various efforts to improve the business environment that attracts foreign investors, especially South Korea. This is proven by Korea as the biggest contributor to Foreign Direct Investment in Vietnam. Keywords: Foreign Development Assistance, Foreign Direct Investment, LOI and LOE, ODA, Strategic Cooperation, WTO.